Advantages of E-Books to the Development of Learners Education (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The ways in which people live, work, and commute have all been changed by technology. Therefore, it should come as no surprise that it has also changed how people learn. Regarding the function eBooks have in education, there are a lot of differing views. This thesis focuses on the advantages of using eBooks in the classroom. Electronic books, or online eBooks, have the potential to simplify, expedite, and lower the cost of education. Find out how eBooks can benefit students' learning in novel and significant ways.